The Mysterious Case of Benton and Gould: America Today and Dick Tracy as Documents of the Great Depression - Melinda Narro (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
This paper explores the close connections that run between American Regionalist art and newspaper adventure comics during the 1930s using Thomas Hart Benton’s America Today mural (1930-31) and Chester Gould’s Dick Tracy strip (1931). These concurrent popular movements each represent a seismic shift in the tone of their medium when compared to that of the 1920s. Within these two works, repeated patterns of form and content attest to a shared purpose rooted in the national malaise of the early Depression. Granted parity as valuable historic documents, both America Today and Dick Tracy speak clearly to the desires, frustrations, and fears of a country in crisis. Further critical reading reveals how Benton and Gould achieved similar levels of popular acclaim by offering the public visual and narrative affirmations of American unity, ingenuity, and strength. The cultural insight gleaned in such an exercise argues for a more holistic approach to art history that eschews “high” and “low” artistic distinctions.